Antibacterial and Antioxidant Activities of Endophytic Fungal Extracts from Pluchea indica (L.) Less. - Adelia Filza Izzati; Suryati; Ahmad Fathoni; Muhammad Ilyas; Andria Agusta (Indonesian Scholar Society, 2026)
This study investigated endophytic fungi associated with Pluchea indica (L.) Less, focusing on their chemical profiles and biological potential. A total of five isolates were successfully obtained from leaves and stems. Morphological examination led us to identified the fungal isolates -as Aspergillus section Nigri 12TBt-3, Colletotrichum sp. 12TDn-1, Diaporthe sp. (Phomopsis sp.) 12TBt-1, Diaporthe sp. (Phomopsis sp.) 12TBt-2, and Diaporthe sp. (Phomopsis sp.) 12TDn-2. Thin-layer chromatography (TLC) analysis revealed distinct secondary metabolite profiles among the isolates, with the detection of alkaloids and phenolic compounds, particularly in extracts Aspergillus section Nigri 12TBt-3 and Diaporthe sp. (Phomopsis sp.) 12TDn2. Antibacterial activity was evaluated qualitatively by TLC bioautography and quantitatively by microdilution assays. Extract Aspergillus section Nigri 12TBt-3 exhibited moderate inhibitory activity against Staphylococcus aureus (MIC 128 µg/mL) and Escherichia coli (MIC 256 µg/mL). Antioxidant activity, assessed using the DPPH assay, demonstrated that the extract Aspergillus section Nigri 12TBt-3 possessed strong activity with an IC50 value of 27.31 µg/mL and an Antioxidant Activity Index (AAI) of 1.14. In addition, total phenolic content analysis revealed that the extract Aspergillus section Nigri 12TBt-3 contained 257.179 mg GAE/g extract, while Diaporthe sp. (Phomopsis sp.) 12TDn2 contained 67.249 mg GAE/g extract. Collectively, these findings indicate that endophytic fungi from Pluchea indica (L.) Less, particularly isolated Aspergillus section Nigri 12TBt-3, harbor significant potential as sources of bioactive metabolites with antibacterial and antioxidant properties, supporting their prospective application in biotechnology and pharmaceutical development.